NPK Fertilizers for Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) Intercropped with Coffee Trees - Santosa, Edi; Susila, Anas Dinurrohman; Lontoh, Adolf Pieter; Noguchi, Arisa; Takahata, Ken; Sugiyama, Nobuo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTFertilizer application in elephant foot yams (Amorphophallus paeoniifolius (Dennst.) Nicolson) intercropping system is rare in Indonesia, therefore, NPK fertilizers experiment was conducted under the shade of 10-year-old coffee plantation at Leuwikopo Experimental Farm, Bogor, Indonesia, in order to increase the productivity of elephant foot yam intercropped with coffee trees. Prior to planting, 20 ton ha-1 of goat manure was applied. Four NPK combinations, i.e., N, P2O5, K2O at the rate of 0, 0 and 0; 100, 60 and 80; 125, 60 and 100; and 150, 60 and 120 kg ha-1, were applied. Results showed that there were no significant differences in leaf number per plant, petiole size and rachis length among treatments. Application of NPK decreased photosynthetic rates, while increasing rate of N and K2O had no effect on photosynthetic rates. NPK application at the 100 N, 60 P2O5 and 80 K2O kg ha-1 (N100P60K80 treatment) or larger prolonged growth duration regardless of NPK levels, and there was a close relationship between corm yield and growth duration. As a result, corm fresh mass was higher in the 100:60:80 kg ha-1 treatment than in control. In the N125P60K100 and N150P60K120 kg ha-1 treatments, leaves were damaged by heavy rains and winds, counteracting beneficial effect of NPK on growth duration and corm yield. These results suggested the importance of delay of entering dormancy for an increase in productivity of A. paeoniifolius.Keywords: NPK fertilizers, photosynthesis, productivity, prolong growth, tuber crop